Snack Product Diversification and E-Wom on Purchasing Decision (Study On E-Commerce Shopee Eateat Gresik in Gresik Regency) - Adinda Rizky Hayu Pangestu; A. Yahya Surya Winata (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
The objective of this study is to explain the snack product diversification, E-Wom and purchasing decision in E-commerce Eateat Gresik. Another objective of this study is to partially explain the effect of snack product diversification, E-Wom and purchasing decision in E-commerce Eateat Gresik. This study uses quantitative method using multiple linear regression analysis. This study uses a probability sampling technique; simple random sampling with a sample of 90 respondents. Based on the results of Product diversification and E-WOM (Electronic Word of Mouth) have a positive and significant effect on the level of purchasing decision to e-commerce shopee of Eateat Gresik.